Ectopic pituitary adenoma located at the pituitary stalk: Case report - (:unkn) unknown (My University, 2005)
Suprasellar located ectopic pituitary adenomas are unusual tumors. We report a rare case of suprasellar prolactinoma arising from the pars tuberalis in a 37-year-old woman. Menstrual deregulation and bitemporal hemianopsia were the main complaints. Blood tests revealed hyperprolactinemia. In magnetic resonance the tumor was totally supradiaphragmatic. Pterional craniotomy and total tumor excision was performed. The pituitary stalk was preserved. Histopathologic diagnosis was a pituitary adenoma immunoreactive for prolactin. Pituitary hormonal functions returned to normal at 6 months postoperatively. No complications were seen in the postoperative period. An ectopic adenoma should be suspected in a patient with suprasellar tumor and hyperprolactinemia. Surgical excision of this tumor may result with normal pituitary functions and normal visual acuity.
Keywords: Ectopic adenoma; Pars tuberalis; Prolactinoma; Suprasellar neoplasms